(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
In this paper, the improved Wei oscillator has been used to model the experimental Rydberg-Klein-Rees data of the X2 Σg+ state of N2+ diatomic ions. Average absolute deviation from the dissociation energy of 0.3211% and mean absolute percentage deviation of 0.6107% were obtained. These results are quite satisfactory since they are within error requirement rate of less than 1% of the Lippincott’s criterion. Using an existing equation in the literature for bound state ro-vibrational energy, expressions for ro-vibrational partition function and mean thermal energy were derived for the improved Wei oscillator within the context of classical physics. The formulas obtained for ro-vibrational partition function and mean thermal energy were subsequently applied to the spectroscopic data of N2+ (X2 Σg+) diatomic ions. Studies have revealed that the partition function of the system decreases monotonically with decrease in temperature and increases with increase in upper bound vibrational quantum number. On the other hand, the mean thermal energies of the diatomic ions show an initial sharp decrease when the temperature is decreased and afterwards remains fairly stable as the temperature is further lowered. The results obtained in this work may find suitable applications in astrophysics were potential energy functions are required to model experimentally determined potential energy data with high precision. The work may also be useful in many other areas of physics which include: chemical physics, molecular physics, atomic physics and solid-state physics